2013
DOI: 10.1007/s10508-013-0121-1
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Explicit Media on the Internet: A Content Analysis of Sexual Behaviors, Risk, and Media Characteristics in Gay Male Adult Videos

Abstract: Recent research suggests that viewing sexually explicit media (SEM), i.e., adult videos, may influence sexual risk taking among men who have sex with men (MSM). Despite this evidence, very little is known about the content of gay male SEM on the Internet, including the prevalence of sexual risk behaviors and their relation to video- and performer-characteristics, viewing frequency, and favorability. The current study content analyzed 302 sexually explicit videos featuring male same-sex performers that were pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 37 publications
1
47
0
Order By: Relevance
“…As the MSM-specific SEOM industry has grown, there has also been an increase in the percentage of MSM-specific SEOM depicting unprotected sex (Downing, Schrimshaw, Antebi, & Siegel, 2013; Grudzen et al, 2009; Hurley, 2009). It has been argued that increasing consumer demand and access to amateur SEOM portraying UAI has created an online market that compels industry production of SEOM portraying UAI (McNeil, 2012; Rosser et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the MSM-specific SEOM industry has grown, there has also been an increase in the percentage of MSM-specific SEOM depicting unprotected sex (Downing, Schrimshaw, Antebi, & Siegel, 2013; Grudzen et al, 2009; Hurley, 2009). It has been argued that increasing consumer demand and access to amateur SEOM portraying UAI has created an online market that compels industry production of SEOM portraying UAI (McNeil, 2012; Rosser et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Despite almost universal SEOM use among MSM (Rosser et al, 2013; Stein et al, 2012) and SEOM’s likely greater portrayal of UAI compared to sexually explicit media distributed in more traditional ways (e.g, DVDs, video tapes, magazines) (Downing et al, 2013; Grudzen et al, 2009), we are only aware of one study that has specifically assessed the association of SEOM as opposed to sexually explicit media more generally, with MSM’s sexual behavior. In a recent daily diary study, Rosenberger (2012) found that MSM were more likely to engage in anal intercourse, oral sex, and oral-anal contact on the days they viewed SEOM compared to days they did not.…”
Section: Introductionmentioning
confidence: 99%
“…Online gay SEM has been reported to play a positive role in the sexuality of men who have sex with men (MSM) by expanding their understanding of their sexual orientation, sexual knowledge, and behavior preferences (e.g., Hald, Smolenski, & Rosser, 2013;Nelson, Leicklya, Yanga, Pereirab, & Simonia, 2014). However, a number of studies have also found an association between frequent use of SEM and several types of sexual risk behaviors (e.g., Downing, Schrimshaw, Antebi, & Siegel, 2014;Eaton, Cain, Pope, Garcia, & Cherry, 2012).…”
mentioning
confidence: 99%
“…For example, viewing SEM may aid in the learning of performing same-sex sex 20,21 ; promote self-recognition of same-sex attractions 20,22 ; and clarify sexual self-labels 23 . However, SEM depicting male same-sex acts often contain several potentially risky sexual behaviors known to be associated with STI risk, including UAI, ejaculation in the mouth (EM), and ejaculation in/on or rubbed into the anus (EA) 24 . Some studies have indicated that viewing SEM is associated with sexual risk behaviors among MSM 25,26 .…”
Section: Sem Consumption and Sexual Risk Behaviors Among Msmmentioning
confidence: 99%
“…Prior studies also tend to focus UAI as either the sexual risk behavior or the behavior of interest as depicted in the SEM 25,26 . However, SEM depicting male same-sex acts often contain several potentially high-risk sexual behaviors including exchange of semen, ejaculation in the mouth (EM) and ejaculation on or around the anus (EA) which require further study 24 .…”
Section: Limitations Of Prior Researchmentioning
confidence: 99%